The Prevalence of Dental Anxiety Associated with Pain among Chinese Adult Patients in Guangzhou - Jiali Yu; Rui Jiang; Er-Min Nie; Chun-Yuan Zhang; Xiang Li (Pain Research and Management)
Background. Anxious people appear to exaggerate the severity of aversive experiences such as anxiety and pain. Anxiety towards dental procedures is a common difficulty that may be experienced by dental patients all over the world. The goal of the study is to find out the prevalence of dental anxiety and its associated factors in Chinese adult patients. Methods. A cross-sectional study was conducted on 183 dental adult patients whose age ranged from 18 to 70 years. Demographic details, first and most recent dental visits with experience, the MDAS, and the Visual Analogue Scale for Anxiety (VAS-A) were obtained. Data were analyzed by frequency analysis, chi-square test, and Spearman correlation test. Results. Most of the respondents were female (68.9%) and 30–45 years age group. The mean total score for dental anxiety on the MDAS was 13.63 (3.1). 80.3% of participants suffered from moderate or high dental anxiety. Age must show a strong association with dental anxiety among the participants (p=0.011). The first dental visit experience, the frequency of the dental visit, most recent dental experience, length of time since the most recent dental visit, and postponement of the dental visit are strongly associated with the MDAS score (p=0.001). Conclusions. The MDAS score exhibits that Chinese adult patients have significant dental anxiety and phobia. Identifying patients with dental anxiety as soon as possible is essential to providing better dental care.